천연기념물 무인도서(칠발도, 사수도, 난도, 홍도)의 번식실태에 관한 연구 - 강정훈(Jeong-Hoon Kang); 강태한(Tae-Han Kang); 유승화(Seung-Hwa Yoo); 조해진(Hae-Jin Cho); 이시완(Si-Wan Lee); 김인규(In-Kyu Kim) (한국조류학회지, 2008)
2008년 5월부터 2008년 10월까지 천연기념물 무인도서 번식지로 지정된 칠발도, 사수도, 난도, 홍도에 대하여 번식조류의 현황과 실태를 조사하였다. 조사결과 칠발도는 바다제비(Oceanodroma monorhis), 슴새(Calonectris leucomelas), 칼새(Apus pacificus) 등 3종이 번식하였으며, 번식 수는 바다제비 20,715.8±5,918.8 (mean±SD)쌍, 슴새는 10쌍, 칼새는 250개체로 나타났다. 사수도는 슴새와 흑비둘기(Columba janthina) 등 2종이 번식하였으며, 번식 수는 슴새 4,052.8±4,377.4쌍, 흑비둘기 70개체로 나타났다. 난도에서는 괭이갈매기(Larus crassirostris) 1종 이 번식하였으며, 번식 수는 14,376.4±4,950.8쌍으로 나타났다. 홍도 역시 괭이갈매기 1종이 번식하였으며, 번식 수는 32,071.9±10,428.3쌍으로 나타났다. 과거와 번식규모의 변화를 보면 칠발도는 큰 변화가 없는 것으로 나타났으며, 사수도는 번식밀도의 경우 전반적으로 감소한 것으로 나타났다. 난도의 경우 큰 변화가 없었으나 홍도의 경우 과거에 비해 3배 이상이 증가하여 번식지 과밀 현상이 나타나고 있었다. 각 섬의 보호 및 관리방안으로 칠발도는 쇠무릎(Achyranthes japonica)에 대한 관리가 필요하였으며, 사수도는 집쥐(Rattus norvegicus)의 구제와 번식밀도가 높은 나대지의 보호가 필요한 것으로 나타났다. 난도와 홍도의 경우 과도한 사람의 출입에 대한 관리가 필요하였으며, 홍도는 집쥐에 대한 구제가 요구되었다. 향후 천연기념물 무인도서 번식지의 지속적인 보호 및 관리를 위해서는 현황 및 번식실태에 대한 주기적이며 지속적인 모니터링이 필요할 것으로 판단된다. From May to October 2008, the investigation was made on the current status of the breeding birds on Chilbaldo, Sasudo, Nando and Hongdo designated as the Natural Monument Islet in Korea. In Chilbado, it was found three species of breeding birds, including Swinhoe's Storm Petrel Oceanodroma monorhis, Streaked Shearwater Calonectris leucomelas and White-rumped Swift Apus pacificus. Its breeding numbers are 20,715.8±5,918.8 (mean±SD) pairs of Swinhoe's Storm Petrel, 10 pairs of Streaked Shearwater, and 250 pairs of White-rumped Swift. In Sasudo, it was found two species of breeding birds, including Streaked Shearwater and Japanese Wood Pigeon. Its breeding numbers are 4,052.8±4,377.4 pairs of Streaked Shearwaters and 70 individuals of Japanese Wood Pigeon Columba janthina. In Nando, it was found one species of breeding bird, named the Black-tailed Gull Larus crassirostris. Its breeding numbers are 14,376.4±4,950.8 pairs. In Hongdo, it was also found one species of Black-tailed Gull. Its breeding numbers are 32,071.9±10,428.3 pairs. From the past changes in breeding scale, Chilbado has shown not so much changes, while Sasudo shown the entire reduction in terms of density of breeding. In the meantime, Nando has also shown no great changes, but Hongdo shown the sign of overcrowded breeding site, increasing more than by 3 times compared to the past. As for the protection and management of each islets, it requires the extermination and management for Japonica Achyranthes japonica in Chilbado, while it requires the exterminate for Norway Rat Rattus norvegicus and the protection of bare soil where the density of breeding is high in Sasudo. In case of Nando and Hongdo, it is necessary to control or restrict excessive access of people to those areas to some degree. And the exterminate for Norway Rat is required for Hongdo. For the purpose of continuous protection and management of Natural Monument Islets as breeding sites in the future, it would be needed to conduct periodic and continuous monitoring of their current status and breeding trends. KCI Citation Count: 11